PICSS - Physically-Inspired Concatenative Sound Synthesis Tool for Continuous Sonic Interaction Design - Guilherme Dias Santos Pimenta (2022)
This project aims to create a concatenative sound synthesis tool for designing sound for continuous interactions. Through computer vision techniques, it allows extrapolation of physical metrics from video for data-driven synthesis, benefitting from the intuitive parametrization of physically informed models and the realistic granularity of foley and sample based techniques. A series of archetypal case studies are recorded and serve as references for the design and development of the tool.